Does function follow organizational form? Evidence from the lending practices of large and small banks - Berger, Allen N.; Miller, Nathan H.; Petersen, Mitchell A.; Rajan, Raghuram G.; Stein, Jeremy C. (Journal of Financial Economics, 2005)
Theories based on incomplete contracting suggest that small organizations have a comparative advantage in activities that make extensive use of “soft” information. We provide evidence consistent with small banks being better able to collect and act on soft information than large banks. In particular, large banks are less willing to lend to informationally “difficult” credits, such as firms with no financial records. Moreover, after controlling for the endogeneity of bank-firm matching, we find that large banks lend at a greater distance, interact more impersonally with their borrowers, have shorter and less exclusive relationships, and do not alleviate credit constraints as effectively.